Environmental Awareness and Public Transport Usage: A Behavioral Approach to Sustainable Mobility - Arif Fakhrudin; You She Melly Ane Dharasta; Yulia Aji Puspitasari; Awan Awan; Yasmudi Yasmudi; Irwina Meilani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Urban transportation systems are increasingly facing environmental challenges due to rapid urbanization, growing vehicle ownership, and excessive reliance on private motorized transport. Promoting public transportation has therefore become an essential strategy for achieving sustainable mobility and reducing environmental impacts. This study aims to examine the influence of environmental awareness on public transport usage by adopting a behavioural approach based on the Theory of Planned Behaviour developed by Icek Ajzen. Specifically, the study investigates how environmental awareness affects attitudes toward public transport, subjective norms, perceived behavioural control, and public transport usage intention, which subsequently influences actual public transport usage behaviour. A quantitative research design was employed using a survey method to collect data from urban residents who have access to public transportation services. A total of 268 valid responses were analysed using Structural Equation Modelling (SEM) to examine the relationships among the study variables. The results reveal that environmental awareness has a significant positive effect on attitudes toward public transport, subjective norms, perceived behavioural control, and intention to use public transportation. Furthermore, the findings confirm that behavioural intention is a strong predictor of actual public transport usage. The structural model demonstrates substantial explanatory power, indicating that psychological and environmental factors play a crucial role in shaping sustainable transportation behaviour. These findings highlight the importance of integrating environmental awareness into transportation policies aimed at promoting sustainable mobility. Increasing environmental education and awareness campaigns may encourage individuals to adopt environmentally responsible travel behaviour and reduce dependence on private vehicles. The study contributes to the literature on sustainable transportation by extending behavioural theory in explaining public transport adoption and providing practical insights for policymakers seeking to promote environmentally friendly urban mobility systems.